PEMANFAATAN LIMBAH KULIT BUAH KAKAO SEBAGAI ADSORBEN UNTUK PENYERAPAN ION LOGAM KROMIUM (VI) PADA LIMBAH ELEKTROPLATING DI BUKITTINGGI - Ulet Putri Hayati; Hendri Sawir (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2017)
The ability of cacao (Theobroma cacao) peels to remove metal ions chromium (VI) from waste water has been investigated. Effect of pH, initial concentration of metal ions solution, contact time, adsorbent mass and particle size of adsorbent with batch method has been studied. The optimum conditions for metal ions chromium (VI) was found at pH 6 with initial concentration of 750 mg/L, contanct time 15 minutes, adsorbent mass 0,1 gram and particle size 32 µm. This optimum conditions have been applied to electroplating waste in Jirek – Bukittinggi, gave capacity of adsorption metal ions chromium (VI) about 0,0776 mg/g and efficiency of adsorption about 84,07 %. Keywords : Cacao (Theobroma cacao) peels, metal ions chromium (VI), adsorbent and adsorption